SISTEM PENGELUARAN BIAYA OPERASIONAL PADA PT BANK BTN (PERSERO) KANTOR WILAYAH V MAKASSAR - Ahmad Firdaus (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2020)
The research aims to find out the Operating Cost Expenditure System at PT Bank BTN (persero) Regional Office V Makassar. The research used descriptive qualitative,where the researcher described the results of observations and analyzed the data. The writing research conducted in March 2019 to May 2019. After analyzing and discussing the problem, the researcher concluded that the Operating Expenditure System at PT Bank BTN (Persero) Makassar V Regional Office arranged in the Order to Pay PT Bank BTN (persero) V Regional Office Makassar. Operating system expenditure on PT Bank BTN (persero) Makassar V Regional Office is for the procurement of goods and services, then price comparisons will be made based on third party offerings, then based on what offer will be agreed in the form of monthly, quarterly, semester or annual. Most of the PKS (cooperation agreements) are in monthly form so that the third partner will collect every month and will be paid by the officer.